Negosiasi Adat dan Syari’at dalam Tradisi Jejer Wuwung Masyarakat Jawa - Amilatunnafi’ah; Siti Maryam Qurotul Aini (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2026)
The jejer wuwung tradition is a form of customary marriage prohibition that remains practiced within Javanese society, particularly in Klurahan Village, Ngronggot District, Nganjuk Regency. This prohibition is based on the parallel position of the roofs of the prospective spouses’ houses, which is believed to bring misfortune if violated. This study aims to analyze the existence of the jejer wuwung tradition, the perspectives of community leaders toward its practice, and its legal status from the perspective of ‘urf in Islamic law. This research employs field research with a qualitative-descriptive approach. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the theoretical framework of ‘urf. The findings indicate that jejer wuwung continues to be observed by part of the community due to cultural inheritance, social pressure, and beliefs regarding the negative consequences of violating customary rules. Community leaders generally view this tradition as a means of maintaining social harmony, although compliance among younger generations is declining. From the perspective of Islamic law, jejer wuwung lacks a basis in the authoritative texts (nash) and may lead to social harm and fatalistic beliefs. Consequently, this tradition is classified as ‘urf fāsid and cannot serve as a valid legal source (ḥujjah shar‘iyyah). This study underscores the necessity of reinterpreting local customs so that positive social values may be preserved without contradicting the fundamental principles of Islamic law.